Fecal microbiota transplantation: whole grain highland barley improves glucose metabolism by changing gut microbiota - Xin Ren; Fulong Zhang; Min Zhang; Yuan Fang; Zenglong Chen; Meili Huan (Food Science and Human Wellness)
Highland barley (HB) is a high-altitude cereal with rich nutritional components and potential health benefits. To clarify its hypoglycemic effect and mechanism, we investigated the effect of whole grain HB and fecal microbiota transplantation (FMT) on glucose metabolism and gut microbiota in high-fat diet and streptozotocin (HFD/STZ)-induced diabetic mice. The results showed that HB (40%) significantly decreased fasting blood glucose and the area under the glucose tolerance curve, significantly increased insulin secretion and improved insulin resistance in HFD/STZ-induced diabetic mice (P < 0.05). Inflammatory factors and blood lipid indices were also significantly alleviated after 12 weeks of 40% HB intervention (P < 0.05). Additionally, beneficial bacteria, such as Bifidobacterium and Akkermansia, were significantly enriched in the gut of diabetic mice after whole grain HB intervention. Meanwhile, the results of further FMT experiments verified that the fecal microbiota after the 40% HB intervention not only significantly increased the relative abundance of Bifidobacterium and Akkermansia but also effectively improved glucose metabolism and alleviated the inflammatory state in HFD/STZ-induced diabetic mice. Collectively, our study confirmed the bridge role of gut microbiota in improving glucose metabolism of whole grain HB, which could promote the development of precision nutrition.